PEMBERDAYAAN EKONOMI BERBASIS STRATEGI PEMASARAN PRODUK LOKAL SERTA PENERAPAN AKUNTANSI PENGELOLAAN KEUANGAN BAGI UMKM KELOMPOK TANI NEKEMOLO, DESA BAUMATA TIMUR, KABUPATEN KUPANG, NUSA TENGGARA TIMUR - Mansuetus Mola; Rozita Yusniaty Lodo; Chamelya Vivi Crystanty Sene (LPPM Universitas Bina Bangsa, 2024)
Community Service Activities (PkM) were carried out in East Baumata village, Central Kupang District, Kupang Regency, East Nusa Tenggara with the target of MSME partners of the Nekemolo Farmer Group. PKM activities are carried out with the aim of providing understanding to partners about the supporting factors of business activities in their villages, namely marketing strategy factors, product legality and financial management so that the business activities carried out are not only profit-oriented, but business activities can continue to grow in the future by paying attention to and applying supporting factors for business activities. To achieve this goal, PKM activities are held in the form of socialization about business legality, especially regarding brands and legality in business activities, product marketing strategies and digital financial management. The socialization is adjusted to the problems and needs faced by MSME partners of the Nekemolo Farmer Group, East Baumata Village, Kupang Regency, East Nusa Tenggara. Partners are also given training on product marketing strategies using digital marketing and financial management using software. The method of carrying out activities consists of three stages. The first stage of preparation includes pre-survey, team building, proposal creation and submission, team and partner coordination and preparation of training tools and materials. The second stage is the program implementation stage in the form of socialization and training. Socialization is carried out through counseling (material presentation) and discussion while training is carried out through tutorials and mentoring. The third stage is the evaluation and reporting stage. Evaluation is carried out by comparing the condition of partners before and after the implementation of the program with interview and observation methods. After that, a report is prepared for further publication. The material presented in socialization is in the form of brands as marketing strategies in business activities, the role of digital marketing as a strategy in product marketing and bookkeeping using software. Training topics include how to register products to get a brand online, creating accounts in digital media and the application of accounting in financial management using software. The results and outputs of activities after socialization are carried out, namely first, partners experience an increase in understanding of the brand and want to register products (brand awareness) as a marketing strategy and partners implement attractive brand creation and